Law as a Means of Serving Justice in Nigeria - Hakeem, Ijaiya Olasunkanmi (Pandecta Research Law Journal, 2018)
Right from the ancient times, the relationship between law and justice constantly appears to be one of the most stimulating as well as penetrating controversial ideas. The paper will discuss the fundamental concept of law and justice by assessing the ideas of a few justice thinkers, some key theories of law and justice, and some cardinal indicators of law and justice with a practical example from Nigeria. The study adopted qualitative research which comprises doctrinal and non-doctrinal methods. The research draws information from primary and secondary sources. The information obtained was subjected to content analysis. The paper found that justice is an inherent component of the law and not separate or distinct from it. The paper also found that the idea of justice has been trapped by political ideologies, religions, cultural intolerance, poverty, deprivation, gender discrimination, violation of human rights and inequality in Nigeria. In quintessence, the paper concludes that law is justice. The paper recommends that the courts should lean on the side of justice in any case of conflict between law and justice for effective administration of justice.